Digital Transformation and Work-Life Harmony: Driving Employee Performance Through Organizational Commitment - Fajar Kartika Syaiful Ulum; Osly Usman (Journal of Digital Business and Global Economy, 2026)
The main aim of the present study is to explore the direct and indirect influence of Work-life Balance and Digitalization on Employee Performance with the mediating role of Organizational Commitment in the Indonesia employment scenario. This quantitative study involved a total of 60 employees. The hypothesis was tested by structural equation modeling (SEM) within the Smart-PLS program. The output showed that Work-life balance doesn't have a big impact on commitment to the company. (t-value: 1.316). Digitalization has a positive and substantial effect on Organizational Commitment (t-value: 5.107). Moreover, the direct effects of both Work-life Balance (t: 0.793) and Digitalization (t: 1.696) on Employee Performance are insignificant. On the other hand, the Organizational Commitment contributes considerably in improving directly the Performance (t-value: 2.471). The data support the mediation study for Work-life Balance and Performance, where Organizational Commitment does not mediate the connection (t: 0.971). However, it is a very important mediator in the relationship between Digitalization and Employee Performance (t-value: 2.073).